Simulation of Memory-Based 1024-Point Fast Fourier Transform for Broadband Wireless Access Technology on FPGA - Dinda Pramanta; Denny Darlis; Iswahyudi Hidayat (IJAIT (International Journal of Applied Information Technology), 2017)
The limited radio frequency spectrum that can be used for transmission leads to bandwidth and power efficiency being a key requirement in the development of wireless access technology from 3G to 5G today. Data communication technology also requires this as mentioned on high speed network standards such as DSL, WLAN and WMAN with its products ADSL, WiFi and Wimax. In the last few decades we have seen the evolution of the Orthogonal Frequency Division Multiplexing (OFDM) modulation technique used in the technologies mentioned earlier to this day. This technique is regarded as a standard technology for broadband wireless access technology. In hardware implementation, the most preferred by many researchers is the Field Programmable Gate Array chip, as it can be reconfigured. The OFDM technique can be easily implemented because it uses Fast Fourier Transform (FFT) algorithms that are coding and programming capable of reducing the computational time of Discrete Fourier Transform. This paper discusses the implementation of the memory-based 1024-point IFFT / FFT for BWA communications. The design is focused on synthesizing and implementing the system block FFT 1024-point radix-4 using Decimation in Frequency (DIF) method. Implementation for IFFT / FFT 1024-point resource usage slice number 1%, the number of slice flip-flop 1%, the number 4 LUT (Look Up Table) 1%, and the number of IOB 27%. of the FPGA are used.